The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.3389/fpain.2023.1306475
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of mastication myalgia—an overview

Golnaz Barjandi,
Johanna Svedenlöf,
Hajer Jasim
et al.

Abstract: Mastication myalgia is the most common cause of non-odontogenic pain in the orofacial region and is often associated with a reduced quality of life. The purpose of this review is to provide an overview of the clinical aspects of myalgia based on available research. The review includes epidemiological, diagnostic, and etiological aspects. In addition, the potential risk factors related to the transition from acute to chronic myalgia are explored and treatment strategies are presented for its management. As a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 114 publications
(159 reference statements)
0
4
0
Order By: Relevance
“…Only two SRs showed a positive effect of BoNT-A [45,46], but only in half of the included RCTs in one of the reviews [46]. Although mandibular movements often are reduced in patients with M-TMD [17] as a consequence to the pain, BoNT-A does not seem to improve the range of mandibular movements, in accordance with a previous network-meta analysis showing that neither dry needling or wet needling with BoNT has a positive effect on mandibular movements [18]. One can only speculate as to why the effect on mandibular movements did not follow the pain-reducing effects shown in these SRs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Only two SRs showed a positive effect of BoNT-A [45,46], but only in half of the included RCTs in one of the reviews [46]. Although mandibular movements often are reduced in patients with M-TMD [17] as a consequence to the pain, BoNT-A does not seem to improve the range of mandibular movements, in accordance with a previous network-meta analysis showing that neither dry needling or wet needling with BoNT has a positive effect on mandibular movements [18]. One can only speculate as to why the effect on mandibular movements did not follow the pain-reducing effects shown in these SRs.…”
Section: Discussionmentioning
confidence: 98%
“…M-TMD is the most common (45%) diagnosis among the TMD diagnoses and is characterized by regional pain and increased tenderness in the masticatory muscles, diminished masticatory performance, and restricted jaw movements [17]. Although several treatment approaches have been shown to be successful in the management of M-TMD [17][18][19][20][21], persistence of pain in the masticatory muscles is common [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some patients, administration of nonsteroidal anti-inflammatory drugs (NSAIDs) for a week (along with drugs to protect the stomach) and a strict soft diet can already bring some relief. Barjandi [ 25 ] et al’s literature review demonstrated that naproxen and ibuprofen are the first choice of NSAIDs in patients at risk for cardiovascular diseases, and if the patient is at risk for gastrointestinal bleeding, celecoxib should be chosen [ 25 ].…”
Section: Discussionmentioning
confidence: 99%